Intestinal strangulation: about 81 observations - Silva, Celso (Cirugía del Uruguay, 2020)
1) 81 cases of human intestinal obstruction were analized of the clinical point of view. 2) The relation among different parameters ( age, sex, types of strangulation, etc.) and the mortality was looked for. 3) The principal letal factors in this entity were pointed out. 4) The principles for improving the results were outlined